HPLC-ESI/MS-MS characterization of compounds in Dolomiaea costus extract and evaluation of cytotoxic and antiviral properties: molecular mechanisms underlying apoptosis-inducing effect on breast cancer - Heba A. S. El-Nashar; Omayma A. Eldahshan; Nasra F Abdel Fattah; Samah A Loutfy; Ibrahim M Abdel-Salam (BMC, 2023)
Abstract Background Dolomiaea costus (syn: Saussurea costus; Family Asteraceae) occupies an important place in the traditional Chinese medicinal plants and is prescribed for a wide range of disorders. The current study aimed to tentatively identify the phytoconstituents of D. costus extract and to explore antiproliferative activity against human breast cancer cells and its possible apoptotic mechanism along with antiviral activity against human adenovirus 5 (Adv-5). Methods The phytoconstituents of 70% ethanol extract of D. costus were assessed using HPLC/ESI-MS/MS technique. The cell viability was investigated against breast cancer cell line (MCF-7) via 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Mechanistically, the apoptotic effects on the Bax, Bcl2 and Caspase 3 were determined via quantitative reverse transcriptase-polymerase chain reaction (RT-qPCR). Further, the antiviral activity was assessed against Adv-5 based on virucidal and adsorption mechanisms. Results The HPLC/MS analysis of the extract revealed tentative identification of twenty compounds of polyphenolic nature, mainly flavonoids, lignans, coumarins, and anthocyanidins. The plant extract showed a cytotoxic effect against MCF-7 and Vero cells with IC50 values of 15.50 and 44 µg/ml, respectively, indicating its aggressiveness against the proliferation of breast cancer cells as confirmed by apoptotic genes expression which revealed upregulation of Bax and Caspase 3 but further insight analysis is needed to explore exact mechanistic pathway. Antiviral activity against Adv-5 was observed at a non-toxic concentration of the tested extract. Conclusions Such observations against human breast cancer and viral replication supported further studies for nanoformulations in drug delivery systems as targeting therapy and in vivo studies before biomedical applications.